Natural Products as Chemopreventive Agents by Potential Inhibition of the Kinase Domain in ErbB Receptors - Maria Olivero-Acosta; Wilson Maldonado-Rojas; Jesus Olivero-Verbel (Molecules, 2017)
Small molecules found in natural products provide therapeutic benefits due to their pharmacological or biological activity, which may increase or decrease the expression of human epidermal growth factor receptor (HER), a promising target in the modification of signaling cascades involved in excessive cellular growth. In this study, in silico molecular protein-ligand docking protocols were performed with AutoDock Vina in order to evaluate the interaction of 800 natural compounds (NPs) from the NatProd Collection (http://www.msdiscovery.com/natprod.html), with four human HER family members: HER1 (PDB: 2ITW), HER2 (PDB: 3PP0), HER3 (PDB: 3LMG) and HER4 (PDB: 2R4B). The best binding affinity values (kcal/mol) for docking pairs were obtained for HER1-podototarin (−10.7), HER2-hecogenin acetate (−11.2), HER3-hesperidin (−11.5) and HER4-theaflavin (−10.7). The reliability of the theoretical calculations was evaluated employing published data on HER inhibition correlated with in silico binding calculations. IC50 values followed a significant linear relationship with the theoretical binding Affinity data for HER1 (R = 0.656, p < 0.0001) and HER2 (R = 0.543, p < 0.0001), but not for HER4 (R = 0.364, p > 0.05). In short, this methodology allowed the identification of several NPs as HER inhibitors, being useful in the discovery and design of more potent and selective anticancer drugs.